An investigation into Anglophone and VietNamese teachers’ encouraging strategies in English class = Nghiên cứu về chiến lược khích lệ của giáo viên các nước nói tiếng Anh và giáo viên Việt Nam trong lớp học tiếng Anh - Phan, Thi Thanh Loan (2020)
In the time of integration, the mutual exchange of education and culture has diversified. The connection between teaching and culture is progressively explored. In the classroom context, the choice of encouragement strategies is a method that deserves careful consideration by both Vietnamese and Anglophone lecturers. Cultural differences can lead to misunderstanding in encouragement and even culture shocks for Vietnamese students during learning from foreign teachers or studying overseas. This study was carried out for the following purposes: investigating verbal and nonverbal strategies that Anglophone and Vietnamese teachers adopt to encourage students in English class, finding out the similarities and differences between Anglophone and Vietnamese teachers’ strategies to encourage students in English lesson. This project is based on two kinds of methods: questionnaire and observation. The result shows that Anglophone and Vietnamese teachers use eleven verbal encouraging strategies: giving positive remarks, expressing positive emotions, reassuring, proposing actions, offering help, asking questions, congratulating, expressing sympathy, promising gift, giving advice and predicting bright future to perform the act of encouraging; and thirteen nonverbal encouraging strategies: smiling, nodding head, keeping a direct eye contact, raising eyebrow, putting hand up, making a thumb-up gesture, clapping hands, leaning the body toward students, turning the body toward students, patting students on the back, patting students on the shoulder, rubbing students’ head, moving closer to students. The similarities and differences are found in the choice of encouraging strategies, the frequency and the effectiveness of encouraging strategies.